2016
DOI: 10.1051/0004-6361/201527213
|View full text |Cite
|
Sign up to set email alerts
|

Surface flux transport simulations: Effect of inflows toward active regions and random velocities on the evolution of the Sun’s large-scale magnetic field

Abstract: Aims. We aim to determine the effect of converging flows on the evolution of a bipolar magnetic region (BMR), and to investigate the role of these inflows in the generation of poloidal flux. We also discuss whether the flux dispersal due to turbulent flows can be described as a diffusion process. Methods. We developed a simple surface flux transport model based on point-like magnetic concentrations. We tracked the tilt angle, the magnetic flux and the axial dipole moment of a BMR in simulations with and withou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 26 publications
1
20
0
Order By: Relevance
“…For all the values of the FWHM, the average amplitude of the axial dipole moment decreases relative to their no-inflows counterpart. This is due to the quenching of the contribution of the BMRs to the global dipole induced by the inflows, which is determined by the magnetic flux of the BMR and the latitudinal separation of the polarities (Martin-Belda & Cameron 2016). The inflows act to enhance the cancellation of opposite polarity flux and limit the latitudinal separation of the polarities, resulting in a reduction of such contribution.…”
Section: Inflow Parametersmentioning
confidence: 99%
“…For all the values of the FWHM, the average amplitude of the axial dipole moment decreases relative to their no-inflows counterpart. This is due to the quenching of the contribution of the BMRs to the global dipole induced by the inflows, which is determined by the magnetic flux of the BMR and the latitudinal separation of the polarities (Martin-Belda & Cameron 2016). The inflows act to enhance the cancellation of opposite polarity flux and limit the latitudinal separation of the polarities, resulting in a reduction of such contribution.…”
Section: Inflow Parametersmentioning
confidence: 99%
“…In flux-transport simulations, the inflows to active regions play an important role in the transport of magnetic flux over the course of the solar cycle. The inflows can affect the dispersal of active regions, since they counterbalance the outward diffusion of magnetic flux by convection (De Rosa & Schrijver 2006;Martin-Belda & Cameron 2016). They are also a potential mechanism for modulating the strength of the solar cycle (Cameron & Schüssler 2012;Shetye et al 2015;Martin-Belda & Cameron 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Corks of opposite polarity that move within 1 Mm of each other are removed from the simulation. The distance threshold is the same as that used by Martin-Belda & Cameron (2016).…”
Section: Cork Simulation For Local Surface Flux Transportmentioning
confidence: 99%
“…Several studies have incorporated inflows around active regions in surface flux transport models (De Rosa & Schrijver 2006;Jiang et al 2010;Cameron & Schüssler 2012;Yeates 2014;Martin-Belda & Cameron 2016. Martin-Belda & Cameron (2016) found that the inflows enhance flux cancellation, and can in conjunction with differential rotation produce a net tilt angle. This tilt is however too small compared with observed tilt angles.…”
Section: Introductionmentioning
confidence: 99%